Analysis of precise behavior characteristics of emulsified fuel - Yoon, Jeong Hwan; Yeom, Jeong Kuk (Journal of mechanical science and technology, 2018)
This study is a basic research on the application of the mixed emulsified fuel of diesel and hydrogen peroxide (H2O2) to the diesel engine and investigating the evaporative characteristics of the emulsified fuel. The surfactant used to mix the emulsified fuel was added by mixing the span 80 and tween 80 with a ratio of 9:1 and being fixed to 3 % of the total volume of the emulsified fuel. The mixing ratio of the emulsified fuel was selected as EF0 (Only diesel), EF2, EF12, EF22, EF32 and EF42, respectively, considering the mixing ratio of the surfactant. To analyze the evaporative characteristics of the emulsified fuel in accordance with the mixing ratio, a drop of the emulsified fuel was freely dropped to a hot plate maintained at 473 K with a spuit and then the experimental results of the drop evaporation were visualized with the Schlieren system. Then, the quantitative image analysis of the images was introduced and it could be found that droplet evaporation was promoted according to the increase of the hydrogen peroxide in the emulsified fuel. Also, numerical analysis was performed with modeling for micro droplets in the fuel based on the experimental result, and promoted-fuel evaporation was reproduced due to the microexplosion of evaporative characteristics of emulsified fuel in accordance with the increase of the mixing ratio of hydrogen peroxide. Also, for quantitative analysis of experimental results, entropy analysis based on statistical thermodynamics was carried out. Consequently, in the case of the application of emulsified fuel to the diesel engine, it is expected to simultaneously decrease the Soot and NOx generation by speedily mixture formation and the latent heat of evaporation of the emulsified fuel in the cylinder.